Obstacle avoidance robot using sonar sensor (OARuS) - Mohamad Sabri Abdullah (Universiti Malaysia Perlis, 2008)
The obstacle-avoidance method is a means to avoid obstacles that exist within the correction area of groping locomotion by applying a suitable algorithm to the humanoid robot’s control system. Some studies on robotics have led to the proposal of an obstacle avoidance method employing non-physical contact, such as sonar sensor, vision navigation and image processing, while others use armed mobile robots and humanoids on a static platform. Obstacle avoidance is also a robot discipline with the objective moving the robot basis of the sensorial information. I choose this type of sensor is because it can send and receive signal only using one sensor. After I test these sensors, I choose to use an LV-MaxSonar@EZ1 as my transducer because these sensors have more advantage such as easy to use, range stability, continuously variable gain, quality beam shape, wave form analysis, calibration and test, very small size (and weight), low cost, low power, and wide operating voltage for this system. For the motor drive, I choose to use L293d to control DC motor driver as H-Bridge circuit. An embedded controller function as total guard actions that made by robot, it will receive, processing, and define data (input), and decide what that should do by robot to further action. I use the Basic Stamp2 as our controller. For this operation, if sensor detect obstacle, robot will move direction no restriction to reach to last post.